Evaluating the Implementation of Modern Navigation Systems to Improve Maritime Safety in Indonesia - Samsul Huda; Trisnowati Rahayu; Muhamad Imam Firdaus (International Journal of Marine Engineering Innovation and Research, 2025)
The Indonesian archipelago is strategically located in the major vessels’ global routes and domestic shipping lanes that lead to dense ship traffic with a mix of challenging navigational conditions, which consequently raises the potential risk of maritime accidents. Modern navigational aids—and the systems used in maritime and aeronautical sectors are just two examples—are now widely recognised to be a key factor for increasing situational awareness, explaining better route planning and decreasing instances of collisions or other hazards. This research assesses the role of these technologies to enhance safety in Indonesian waters and explores legal frameworks for their introduction. Through a descriptive/analytical approach supported by regulation review and literature analysis, the study recognizes existing advantages provided modern navigation systems, in real time monitoring and hazards detection in particular. Several challenges remain, however, with the uneven technological uptake among ships and ship types, limited seafarer skills, insufficient navigational infrastructure and evidence of unsafe operation such as AIS switching off. Regulatory loopholes and insufficient harmonization with international regulations (SOLAS, MARPOL, IMO, STCW) also have impacts on the overall effectiveness of navigation technologies. It is concluded that modern navigation systems greatly contribute towards the safety of maritime navigation, but their full utilization will have to be supported by better enforcement of regulations, upgrading infrastructure, regular training of crews and harmonization with national e-navigation initiatives. Recommendations and research directions are suggested in the evaluation to enhance an effective and technological-based maritime safety system in Indonesia.